A Thermoelectric Energy Harvester with a Cold Start of 0.6 °C. (2015) - Mullen, P.; Siviter, J.; Montecucco, A.; Knox, A.R.
Abstract: This paper presents the electrical and thermal design of a thermoelectric energy harvester power system and its characterisation. The energy harvester is powered by a single Thermoelectric Generator (TEG) of 449 couples connected via a power conditioning circuit to an embedded processor. The aim of the work presented in this paper is to experimentally confirm the lowest ΔT measured across the TEG (ΔTTEG ) at which the embedded processor operates to allow for wireless communication. The results show that when a temperature difference of 0.6 °CΔTTEG is applied across the thermoelectric module, an input voltage of 23 mV is generated which is sufficient to activate the energy harvester in approximately 3 minutes. An experimental setup able to accurately maintain and measure very low temperatures is described and the electrical power generated by the TEG at these temperatures is also described. It was found that the energy harvester power system can deliver up to 30 mA of current at 2.2 V in 3ms pulses for over a second. This is sufficient for wireless broadcast, communication and powering of other sensor devices. The successful operation of the wireless harvester at such low temperature gradients offers many new application areas for the system, including those powered by environmental sources and body heat.